Conceptualization Of A Leadership Learning Model For Medical Curriculum: Mix Approaches, Literature Review & Qualitative Case Study - Noor Azura Mat Said; Nur Nabilah Abu Bakar; Wan Shahida Wan Sulaiman; Wan Noraini Wan Sulaiman; Ku Mastura Ku Mohd Noor; Tan Ka Liong; Zatul ‘Iffah Abu Hassan; Azlina Ab Rani; Nadeeya'ayn Umaisara Mohamad Nor (Universiti Sains Islam Malaysia, 2024)
Sains Insani, Volumw 9 Issue 2 Page (171-183)